Implementation of the National Project «Labor Productivity and Employment Support» in the Perm Region: Facts, Problems, Prospects - T. V. Alexandrova; V. L. Popov (Управленческое консультирование)
In the context of the reorientation of the Russian economy towards an innovative development path, the issue of increasing labor productivity has become an important part of state policy.Currently, the country is implementing a large-scale national project «Labor productivity and employment support». The implementation of the project approach to managing labor productivity for the Russian economy is of strategic priority, since its application helps to increase the efficiency of resource use, realize the goals of modernizing production, and stimulate innovation and export activities of domestic enterprises.The aim of the study is to consider the regional aspect of the implementation of the priority national project «Labor productivity and employment support» on the example of the Perm region. The methodological basis of the study are comparative, statistical and expert methods.The paper analyzes the implementation of the national project «Labor productivity and employment support» in the Perm region; presents the actual results of the project; formulates problems in the implementation of project activities; identifies the prospects of the Perm region in the context of setting higher targets for the regional project «Labor productivity and employment support» in comparison with the figures for Russia as a whole.The materials outlined in this article can deepen knowledge about the specifics of the implementation of the priority national project «Labor productivity and employment support» at the regional level, as well as be used to adjust the course implementation of a regional project aimed at improving productivity in the Perm region.